Strategi Optimalisasi Kinerja Dalam Program Pendaftaran Tanah Sistematis Lengkap (PTSL) - Rahayuning Versi Setyawati; Eka Askafi (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
The current land certification policy initiated by the government is based on the Minister of Agrarian and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia Number 06 of 2018 concerning the Complete Systematic Land Registration (PTSL) which targets 126 million certified parcels in all regions of Indonesia in 2025. In the level of the implementation of PTSL at the Land Office of the Tulungagung Regency, it shows that from November 2019 the Tulungagung District Land Office has completed 24,432 land parcels of 32,000 targeted land parcels. The process of achieving targeted land parcels is influenced by internal and external factors of the land office that need to be addressed immediately, including Human Resource factors and limited facilities and general public response. In addition, the Performance optimization strategy needs to be supported by adequate resources and also needs to create a new strategy in resolving internal and external barriers that also come from the competency of community.